Anatomy of a refugee workshop: Syrian labourers in Istanbul - Gaye Yilmaz; Diyar Erdogan (International Labour Organization (ILO), 2019)
There is no doubt that any work carried out with refugees requires much greater sensitivity and care than others. On the other hand, if these studies have to be done with limited budgets in a very limited time, it may be harder to reach meaningful results without sacrificing the necessary sensitivity. Unlike many other works which solely focus on the results, in this study, we aim to bring to light the proceedings of a refugee labour workshop, collaboratively organized by Global Labour University (GLU) Alumnis in Turkey, the ICDD and Kassel University, which, though operated within a limited timeframe and a stringent budget, attained unexpected positive results. While we were coordinating and organizing this workshop, we also came to a conclusion that labour studies may not necessarily be done only through field researches which demands extensive human and financial resources. Indeed, we found that a well-planned workshop, supported with special techniques and ethical concerns may well replace field research in terms of the results achieved. We, therefore, present the background of the Syrian refugee labour workshop held in Istanbul/Boægaziçi University in February 2017 so that similar such endeavours may be undertaken in future when time and resources are limited.
Keywords: 330